Fear of Terrorism and Fear of Violent Crimes in the United States: a Comparative Analysis - Onat, Ismail (Crime & delinquency, 2023)
The purpose of this study was to compare Americans? fear of terrorism to fear of violent crimes (i.e., murder, mass shooting, and gang violence). Previous research suggested that similarities exist between terrorism and violent crimes, yet no study has compared the fear aspects of terrorism and violence in the United States. Using nationally representative data from the 2018 Americans? Fears Survey (N?=?1,190), we compared fear of terrorism to fear of violent crimes with a main focus on the effects of exposure to the media, political views, and religiosity of the adult Americans. The results of the analyses showed the roles of online media, religiosity, and politics differed significantly in shaping the sampled Americans? fear of terrorism when compared to their fear of violent crimes. Despite the resemblance of terrorism and violence, the fear arising from the political nature of terrorism as a crime distinguishes the nature of fear from violent crimes.